Developing co‐operative transport system and route planning - Szűcs, Gábor (Transport, 2009)
This paper consists of two parts: planning Co‐operative Transport Systems (CTS) with general rules (communication is a new idea in this system) and an investigation into route planning as a part of services provided in CTS. Part one reveals developing new systems for cooperative sensing and predicting flow, infrastructure and environmental conditions surrounding traffic, with a view to improve the safety and efficiency of road transport operations. Part two introduces the enhancement of the performance of the route planning algorithms. The key issues of these parts are communication and co‐operation between the elements of the whole Co‐operative Transport System. First published online: 27 Oct 2010